Sustainable Banking Practices and Cost Efficiency: Evidence on Profitability from Islamic Commercial Banks in Indonesia - Fathihani; Sulistiyowati, Rini; Kusuma, Hendra (LP2M IAIN Palopo, 2025)
This study aims to examine the effect of green banking implementation and operational cost efficiency on the profitability of Islamic Commercial Banks in Indonesia during the period 2020–2024. The variables used in this study include green banking as an exogenous variable, operational efficiency (BOPO) as an independent variable, and return on assets (ROA) as a measure of profitability. This quantitative study employs secondary panel data sourced from the annual reports of Islamic Commercial Banks registered with the Financial Services Authority (OJK). The analysis uses a path model approach. The results reveal that green banking has a positive and significant effect on ROA while BOPO has a significant negative effect on ROA. Simultaneous testing found that the implementation of green banking as measured by GCR and BOPO had a positive and significant influence on ROA.These findings indicate that sustainable banking practices and cost efficiency play a critical role in enhancing the financial performance of Islamic banks in Indonesia.